Origin and evolution of the spanish language in Latin America - Корбозерова, Ніна Миколаївнаївна (Київський національний університет імені Тараса Шевченка, 2025)
The article investigates the historical background, sociolinguistic factors, and structural-linguistic consequences of the formation of the Spanish language in Latin America. It examines the process of shaping the American variety of Spanish as a result of prolonged colonial development, intensive contact with indigenous languages, and continuous interaction between European and local cultural codes. The study identifies the main stages in the evolution of Spanish from the period of the conquest to the present day and characterizes its phonetic (seseo, yeísmo, /s/ elision, /n/ velarization), morphological (voseo, ustedeo), and lexical (indigenisms, archaisms, anglicisms) features. Particular attention is given to the issue of linguistic interference, bilingualism, and the influence of indigenous substrates (Nahuatl, Quechua, Guaraní) on the phonetic and grammatical structure of the language. It is shown that the varieties of Spanish in different regions of the Americas (the Caribbean, the Andes, the Río de la Plata, and Central America) form a polycentric system with consolidated internal norms. A comparison of the features of American Spanish with the southern dialects of Spain (Andalusian and Canarian) makes it possible to identify archaic features and regularities of typological affinity. The study deepens the current understanding of the variation and polycentric nature of the Spanish language, revealing the dynamics of linguistic identity formation under conditions of multilingualism and cultural interaction. The methodological basis of the research combines historical-comparative, typological, areal, and sociolinguistic analyses, ensuring a comprehensive approach to the object of study. The results obtained have practical significance for the teaching of comparative linguistics, linguistic cultural studies, and Romance philology and may also be applied in further research on language contact, language policy, and sociolinguistic typology.

У статті досліджено історичні передумови, соціолінгвістичні фактори та структурно-мовні наслідки формування іспанської мови в Латинській Америці. Розглянуто процес становлення американського варіанта іспанської як результат тривалого колоніального розвитку, інтенсивних контактів із автохтонними мовами та постійної взаємодії між європейським і місцевим культурними кодами. У роботі визначено основні етапи еволюції іспанської мови від періоду конкісти до сучасності, охарактеризовано фонетичні (сесео, єїзм, елізія /s/, веляризація /n/), морфологічні (восео, устедео) та лексичні (індигенізми, архаїзми, англіцизми) особливості американського іспанського. Особливу увагу приділено проблемі мовної інтерференції, білінгвізму та впливу індіанських субстратів (науатль, кечуа, гуарані) на фонетичну й граматичну структуру мови. Показано, що варіанти іспанської в різних регіонах Америки (Кариби, Анди, Ріо-де-ла-Плата, Центральна Америка) утворюють поліцентричну систему з усталеними внутрішніми нормами. Здійснено порівняння рис американського іспанського з південними діалектами Іспанії (андалузьким і канарським), що дозволяє виявити архаїчні риси та закономірності типологічної спорідненості. Дослідження поглиблює сучасне розуміння варіантності іспанської мови та її поліцентричного характеру, розкриваючи динаміку становлення мовної ідентичності в умовах багатомовності та культурної взаємодії. Методологічною основою роботи є поєднання історико-порівняльного, типологічного, ареального й соціолінгвістичного аналізу, що забезпечує комплексність підходу до об’єкта дослідження. Отримані результати мають практичне значення для викладання порівняльного мовознавства, лінгвокультурології та історичної романістики, а також можуть бути використані у подальших дослідженнях міжмовних контактів, мовної політики й соціолінгвістичної типології

En el artículo se investigan los antecedentes históricos, los factores sociolingüísticos y las consecuencias estructurales y lingüísticas de la formación del idioma español en América Latina. Se examina el proceso de configuración de la variante americana del español como resultado de un prolongado desarrollo colonial, de los contactos intensos con las lenguas autóctonas y de la interacción constante entre los códigos culturales europeos y locales. El trabajo identifica las principales etapas de la evolución del español desde el período de la conquista hasta la actualidad, y caracteriza sus particularidades fonéticas (seseo, yeísmo, elisión de /s/, velarización de /n/), morfológicas (voseo, ustedeo) y léxicas (indigenismos, arcaísmos, anglicismos). Se presta especial atención al problema de la interferencia lingüística, el bilingüismo y la influencia de los sustratos indígenas (náhuatl, quechua, guaraní) en la estructura fonética y gramatical del idioma. Se demuestra que las variantes del español en las diferentes regiones de América (el Caribe, los Andes, el Río de la Plata y Centroamérica) constituyen un sistema policéntrico con normas internas consolidadas. Se realiza además una comparación de los rasgos del español americano con los dialectos meridionales de España (andaluz y canario), lo que permite identificar rasgos arcaicos y regularidades de afinidad tipológica. El estudio profundiza la comprensión actual de la variación del español y de su carácter policéntrico, revelando la dinámica de formación de la identidad lingüística en condiciones de multilingüismo e interacción cultural. La base metodológica del trabajo combina el análisis histórico-comparativo, tipológico, areal y sociolingüístico, lo que garantiza un enfoque integral hacia el objeto de estudio. Los resultados obtenidos tienen un valor práctico para la enseñanza de la lingüística comparada, la lingüística cultural y la filología románica, y pueden emplearse en investigaciones posteriores sobre los contactos lingüísticos, la política lingüística y la tipología sociolingüística.
Походження та еволюція іспанської мови в Латинській Америці
Origen y evolución del español en LatAm
Keywords: Spanish language; Latin America; linguistic interference; bilingualism; areal differentiation; indigenisms; historical evolution; polycentrism; variationism; іспанська мова; Латинська Америка; мовна інтерференція; білінгвізм; ареальна диференціація; індигенізми; історична еволюція; поліцентризм; варіантологія; lengua española; América Latina; interferencia lingüística; bilingüismo; diferenciación areal; indigenismos; evolución histórica; policentrismo; variacionismo